The Value of Flexible Work: Evidence from Uber Drivers - Chen, M. Keith; Chevalier, Judith A.; Rossi, Peter E.; Oehlsen, Emily (Journal of Political Economy, 2019)
Technology has facilitated new, nontraditional work arrangements, including the ride-sharing company Uber. Uber drivers provide rides anytime they choose. Using data on hourly earnings and driving, we document driver utilization of this real-time flexibility. We propose that the value of flexibility can be measured as deriving from time variation in the drivers' reservation wage. Measuring time variation in drivers' reservation wages allows us to estimate the surplus and labor supply implications of Uber relative to alternative, less-flexible work arrangements. Despite other drawbacks to the Uber arrangement, we estimate that Uber drivers earn more than twice the surplus they would in less-flexible arrangements.